2016
DOI: 10.1080/19491034.2016.1157674
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of the FC/DFC units in nucleoli

Abstract: The essential structural components of the nucleoli, Fibrillar Centers (FC) and Dense Fibrillar Components (DFC), together compose FC/DFC units, loci of rDNA transcription and early RNA processing. In the present study we followed cell cycle related changes of these units in 2 human sarcoma derived cell lines with stable expression of RFP-PCNA (the sliding clamp protein) and GFP-RPA43 (a subunit of RNA polymerase I, pol I) or GFP-fibrillarin. Correlative light and electron microscopy analysis showed that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…In the control the incorporated FU is accumulated predominantly in the nucleolar beads which, according to our earlier study, [55] correspond to the FC/DFC units of the nucleoli (Fig 1). The transcription signal in the nucleoplasm appeared as multiple small foci of much lower intensity.…”
Section: Effects Of Low Temperature On the Nucleolar Transcriptionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the control the incorporated FU is accumulated predominantly in the nucleolar beads which, according to our earlier study, [55] correspond to the FC/DFC units of the nucleoli (Fig 1). The transcription signal in the nucleoplasm appeared as multiple small foci of much lower intensity.…”
Section: Effects Of Low Temperature On the Nucleolar Transcriptionsupporting
confidence: 67%
“…BrUTP (Sigma) was introduced into cells by the scratch procedure. [55,56] Here we followed the same procedure as for the labelling of replication in the cited works. Briefly, the cells were grown on the coverslips; a drop of medium containing 20μg/ml BrUTP was applied upon each coverslip; then the latter was scratched by the tip of a syringe needle and incubated for 5 min at 37˚C.…”
Section: Labeling Of the Transcription Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that correlation of replication timing and Pol I occupancy suggests that a considerable subset of ribosomal genes remain transcriptionally silent from mid S phase to mitosis, but become again active in the postmitotic daughter cells (Smirnov et al 2016). …”
Section: Human Rdna Nucleolar Morphology and Rrna Transcriptionmentioning
confidence: 99%
“…For instance, it is still debatable whether rRNA transcription takes place at FC, DFC, or the border between FC and DFC (Raska et al, 1989;Cheutin et al, 2002;Huang, 2002;Koberna et al, 2002;Raska, 2003;Thiry and Lafontaine, 2005). Observations based on EM have built the foundation of nucleolus structure (Tao et al, 2002;Olson and Dundr, 2005;Derenzini et al, 2006;Cmarko et al, 2008;Thiry et al, 2011;Smirnov et al, 2016). Given that nucleolus is a highly dynamic structure, systematic investigation of nucleolar structure during the cell cycle is still urgently needed.…”
Section: Structural Dynamics Of Nucleolus During the Cell Cyclementioning
confidence: 99%